Adventures in Social Research - Earl Babbie, Fred Halley, Jeanne Zaino (Pine Forge, 2007)
Adventures in social research : Data analysis using SPSS 14.0 and 15.0 for Windows, 6th Edition guides readers step-by-step through the process of data analysis using the latest versions of SPSS and the most up-to-date version of the General Social Survey. In this thoroughly revised edition , authors Earl Babbie, Fred Halleym and Jeanne Zaiono stress active and collaborative learning as students engage in a series of practical investigative exercises.